FACTOR ANALYSIS OF TOURISM APPS FEATURES BY TOURIST IN KUCHING, SARAWAK - Qistina Donna, Lee Abdullah; Aimuni Athirah, Latif (Aliva Global Research and Development, 2021)
This paper highlights the factor analysis of tourism apps features that anticipate the needs and demands of travelers. Dumping of apps that emphasized how to develop the tourism industry and can promote the arts, culture, and heritage in facilitating the travel organization by promoting their business. Producing apps need absolute research on needs and demands of inbound and outbound tourist. Objectives of this paper to identify the features of tourism Apps throughout travel needs and tourism attractions. Second is to propose the features of tourism Apps for tourists and travel agencies in Kuching, Sarawak.Because of that matter, this paper shows the items need in features of tourism apps. Quantitative method used to collect the data then analyze factor analysis using Statistical Package for Social Science. According to the findings find out there are four features in tourism apps should be includes, natural attraction, accommodation, facilities then activities and safety. The tourism industry is a wide field, before certain products are produced and certain services are offered, the producers need to analyze so the product and services can meet target market desire and demands.